The influence of core-build up materials on biaxial flexural strength of monolithic strength-gradient zirconia; an in-vitro study - Dina B. Musa; Nadia S. Ereifej (BMC, 2023)
Abstract Background Since their introduction, there has been limited research regarding the mechanical properties of novel strength-gradient monolithic zirconia. In addition to that, studies evaluating the effect of different core-build materials on the strength of indirect restorations are scarce. Therefore, the aim of this study was to investigate the effect of using different core build-up materials on biaxial flexural strength of a new monolithic multilayered zirconia material. Methods Forty zirconia discs were fabricated from IPS e.max ZirCAD Prime (Ivoclar Vivadent AG, Schaan, Liechtenstein) and divided into 2 groups (n = 20). Forty composite discs were prepared from Tetric N-Ceram (Ivoclar Vivadent AG, Schaan, Liechtenstein) and MultiCore Flow (Ivoclar Vivadent AG, Schaan, Liechtenstein). The zirconia discs were adhesively cemented to the 2 types of composite forming 2 groups (Zirconia-Tetric N-Ceram and Zirconia-MultiCore Flow). Biaxial flexural strength was determined using a piston-on-3-ball test. The data were statistically analyzed with an independent t-test for significant differences (p = 0.05). Results Tetric N-Ceram had significantly higher strength than MultiCore Flow (p < 0.001) but no statistically significant differences were found in strength values between Zirconia-Tetric N-Ceram and Zirconia-MultiCore Flow bilayered samples (p = 0.27). Conclusions It was concluded that although the tested composite core materials significantly differ in their biaxial flexural strength values, they had no influence on the biaxial flexural strength of the overlying zirconia.